Porosity Depth Saturation (PDS) model: Quantification of porosity preservation with burial in carbonate oil reservoirs, and application to infer oil charging time. (October 2020) - Perrin, Christian; Marquez, Xiomara; Flores, Jonatan; Berthereau, Guillaume
Abstract: Oil saturated carbonate reservoirs typically display anomalously high porosities compared to their water filled counterparts, and this has been largely documented in the literature. Nevertheless, no porosity model has been proposed yet to quantify the evolution of porosity preservation by oil under burial. This paper presents a Porosity Depth Saturation model (PDS model) for carbonate reservoirs, that quantifies for the first time the evolution of porosity with depth and oil saturation for a given charging time. The PDS model formulation decouples compaction from porosity preservation. The mechanical and chemical compaction is defined phenomenologically from the Schmoker and Halley (1982) compaction trend, but applied to the water domain only. The computation of the porosity preservation is based on 2 new concepts: the porosity preservation potential that is solely a function of time of charge, and the porosity preservation α factor that is a function of fluid saturation. The work focuses on a large and laterally homogeneous carbonate reservoir. The relations between porosity, oil saturation and depth are extracted from the associated reservoir geomodel and analyzed to define the porosity preservation α factor. The PDS model is tested on a specific reservoir facies and provides the porosity evolution with depth and saturation at any time of charge. It indicates that even at a low water saturation, such as irreducible water condition of an oil reservoir, a reduced amount of water still suffice to reduce somewhat the porosity with burial. From the current reservoir condition, it is shown that the PDS model, solely based on porosity, depth and residual water saturation, can back-calculate the time of charge of a reservoir. Not only the PDS model proposes an initial time of charge in line with the findings of an independent study, but it can also provide relative and quantified charging time for the various zones within the reservoir, offering a level of granularity never achieved before. Highlights: The PDS model quantifies the Porosity evolution with Depth and hydrocarbon Saturation for carbonate reservoirs. Two new concepts are defined: 1) Porosity Preservation Potential: a function of time of charge; 2) Porosity Preservation α Factor: a function of saturation. From current reservoir conditions, the PDS model can infer the burial depth at time of charge. Complemented with a seismic section, the PDS model can infer the time of charge of each compartment within a reservoir.